2016
DOI: 10.1261/rna.057836.116
|View full text |Cite
|
Sign up to set email alerts
|

Efficient in situ detection of mRNAs using the Chlorella virus DNA ligase for padlock probe ligation

Abstract: Padlock probes are single-stranded DNA molecules that are circularized upon hybridization to their target sequence by a DNA ligase. In the following, the circulated padlock probes are amplified and detected with fluorescently labeled probes complementary to the amplification product. The hallmark of padlock probe assays is a high detection specificity gained by the ligation reaction. Concomitantly, the ligation reaction is the largest drawback for a quantitative in situ detection of mRNAs due to the low affini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…As reported earlier, we also observed a high rate of non-cellular amplicons with SplintR ligase 19 | P a g e concentrations above 1 µM 22 . RCA mix consisting of 0.6 U/µl of Phi29 Polymerase (Lucigen, 30221-2) in 1X Phi29 polymerase buffer, 0.25 mM dNTPs, in DEPC treated water was added immediately after ligation step.…”
Section: High-content Boloramis Assaysupporting
confidence: 86%
“…As reported earlier, we also observed a high rate of non-cellular amplicons with SplintR ligase 19 | P a g e concentrations above 1 µM 22 . RCA mix consisting of 0.6 U/µl of Phi29 Polymerase (Lucigen, 30221-2) in 1X Phi29 polymerase buffer, 0.25 mM dNTPs, in DEPC treated water was added immediately after ligation step.…”
Section: High-content Boloramis Assaysupporting
confidence: 86%
“…Two recent papers 35 , 36 reported that in situ RCA can detect eukaryotic mRNA using a padlock probe and SplintR ligase. Previously, RCA for detecting eukaryotic mRNA was performed after RT using target-specific primers 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme is a DNA ligase encoded by Paramecium bursaria Chlorella virus 1, first discovered by Ho et al,(29). A number of studies have successfully applied SplintR ligase for RNA species detection in cultured cells (26, 3032). However, the fidelity of SplintR ligation in end-joining is questionable because it tolerates mismatches at the padlock probe junction and its usefulness is debated.…”
Section: Introductionmentioning
confidence: 99%